2007
DOI: 10.1128/aac.00723-07
|View full text |Cite
|
Sign up to set email alerts
|

Activity of a Potent Hepatitis C Virus Polymerase Inhibitor in the Chimpanzee Model

Abstract: A-837093 is a potent and specific nonnucleoside inhibitor of the hepatitis C virus (HCV) nonstructural protein 5B (NS5B) RNA-dependent RNA polymerase. It possesses nanomolar potencies in both enzymatic and replicon-based cell culture assays. In rats and dogs this compound demonstrated an oral plasma half-life of greater than 7 h, and its bioavailability was >60%. In monkeys it had a half-life of 1.9 h and 15% bioavailability. Its antiviral efficacy was evaluated in two chimpanzees infected with HCV in a proof-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 26 publications
(41 reference statements)
0
28
1
Order By: Relevance
“…The usefulness of the replicon system for HCV mutant study has been demonstrated by previous work, and overall there is a good correlation between in vitro selection of drug-resistant variants in the replicon and mutants selected in drug-treated patients (1,5,6,13,20,22). Still, the results of this study are based on a genotype 1b N strain replicon system which does not represent the genetic backgrounds of all other strains and genotypes, and so the RC profiles of these mutants might change in different genetic backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…The usefulness of the replicon system for HCV mutant study has been demonstrated by previous work, and overall there is a good correlation between in vitro selection of drug-resistant variants in the replicon and mutants selected in drug-treated patients (1,5,6,13,20,22). Still, the results of this study are based on a genotype 1b N strain replicon system which does not represent the genetic backgrounds of all other strains and genotypes, and so the RC profiles of these mutants might change in different genetic backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Further assessment of these analogs, using enzyme isolates and intergenotypic chimeric replicons derived from clinical iso-lates, revealed that the genotypic coverage of the NNI-1 and -4 analogs extends beyond genotype 1, unlike the NNI-2 and -3 derivatives that typically inhibit genotype 1 only (16,38). An additional drawback stems from the lower genetic barrier of the NNI-2 and -3 analogs in genotype 1 (25) and the reduced susceptibility in subtype 1a of the NNI-3 series (7,16,34,38,43). This effect was mostly attributed to the Y415F polymorphism observed in the NNI-3 binding site in subtype 1a (38).…”
mentioning
confidence: 99%
“…These include the poor fidelity and lack of exonucleolytic proofreading capacity of the reverse transcriptase (RT) enzyme in the case of HIV (error rate, 10 Ϫ5 mutations per nucleotide per genomic replication) (4) or the RdRp in the case of HCV (error rate, 10 Ϫ3 to 10 Ϫ5 mutations per nucleotide per genomic replication) (9) and the very high magnitude of replication (HCV, 10 12 virions/day [48]; HIV, 10 10 virions/day [51]). As a result, multiple viral variants known as quasispecies (4,59) are generated.…”
mentioning
confidence: 99%